Where pseudo-hallucinations meet dissociation: a cluster analysis. (August 2017) - Wearne, Deborah; Curtis, Guy J; Genetti, Amanda; Samuel, Mathew; Sebastian, Justin
Objectives: The possible link between cognitive areas of perception and integration of consciousness was examined using assessments of hallucinations and derealisation/depersonalization. Methods: Sixty-five subjects in three main diagnostic groups – posttraumatic stress disorder (PTSD), borderline personality disorder (BPD) and schizophrenia – identified by their treating psychiatrist as hearing voices were surveyed regarding characteristics of hallucinations, derealisation/depersonalization, delusions and childhood/adult trauma. Results: A cluster analysis produced two clusters predominantly determined by variables of hallucinations measures, childhood sexual abuse and derealisation/depersonalization scores. Conclusions: History of childhood trauma and variability in derealisation/depersonalization scores were better predictors of external, negative, uncontrollable voices than diagnosis of BPD or PTSD. The potential links between dissociative states and pseudo-hallucinations are discussed.